Perencanaan Pembangkit Hybrid Optimal Di Grid 3 Nusa, Pulau Nusa Penida - I Gede Putu Oka Indra Wijaya; Sudarmono Sasmono; Wahmisari Priharti (eProceedings of Engineering, 2022)
Abstract—Currently on the island of Nusa Penida only electricity is supplied from the diesel electric power plant Kutampi. The plan is that in 2022 there will be an additional source of electricity that comes from PV solar energy. In addition to the two power plants already mentioned, this study will examine the option of adding wind power plant. The characteristics of renewable energy generators are intermittent and non-dispatchable, so a BESS (battery energy storage system) is also used as power smoothing and frequency control. The planning for the optimal hybrid power plant in Nusa Penida aims to increase the contribution of renewable energy and reduce the COE (Cost of Electricity) lower than the existing COE of Diesel Power Plant in 2018, that is 19 cent/kWh. As well as testing the stability of the system frequency with the allowable range according to the Java, Madura, and Bali Grid Code, which ranges from 49.0 Hz – 51.0 Hz. Keywords—Nusa Penida, diesel electric power plant, PV solar energy, wind power plant, BESS, hybrid power plant, renewable energy, optimal